A Geomimetic Synthesis of Mellite: A Mineral Containing a Benzene Ring. (May 2015) - Plater, M. John; Harrison, William T. A.
The synthesis of mellite from mellitic acid, KOH and Al2 (SO4 )3 18H2 O is demonstrated and discussed as a potential geomimetic process for the formation of the mineral mellite in brown coal. The single crystal structures and IR spectra of the mineral mellite and of synthetic mellite are identical.